A non‐isolated high step‐up MIMO DC–DC converter for renewable energy applications. Issue 10 (27th March 2022) - Azmoon‐Asmarood, Saeed; Maalandish, Mohammad; Shoghli, Ibrahim; Nazemi‐Oskuee, Seyed Hamid Reza; Hosseini, Seyed Hossein
Abstract: This article offers a non‐isolated DC–DC converter with dual‐ports for input and dual‐ports for output with high step‐up ability. The converter has different levels of output voltage. The benefits of the proposed topology consist of the capability of giving high voltage gains with low duty cycle amount, the simple control of each duty cycle, and low per‐unit peak voltage stress (PPVS) over the semiconductors. The presented structure is suitable for clean energy applications. The operation principles, steady‐state analysis, voltage, and current equations extraction in continuous conduction mode (CCM) are carried out. To confirm the superiority of the proposed topology, the efficiency of the converter is compared to other multi‐input (MI) and multi‐output (MO) converters which were recently published in the literature. Eventually, an implemented prototype in the laboratory is used to verify the performance of the proposed structure.